Tanggung Jawab Promotor Perseroan Terbatas Terhadap Kontrak Pra Inkorporasi Di Indonesia - Xavier Nugraha; Ave Maria Frisa Katherina (Media Iuris, 2019)
Ratification of a legal entity based on the issuance of a Decree of the Minister of Law and Human Rights requires a process that is not brief. Meanwhile, corporation which has not been ratified as a legal entity does not rule out the possibility that the promotors of corporation will carry out legal actions in the name of corporation. This journal aims to provide an explanation of the extent to which the liability of corporation and promoters on contracts made before corporation becomes a legal entity. The research methods in this study are conceptual approach and statute approach. Law Number 40 of 2007 concerning Limited Liability Companies in Indonesia currently regulates the liability of promotors before corporation becomes a legal entity. From this journal, it will be known that liability which appears from pre-incorporation contract lies on promotor before corporation becomes a legal entity, but when the legal action has been approved by the General Meeting of Shareholders or has been stated in the deed of establishment, it will become corporate's actions, therefore the liability is also attached.